A Successful Case of In Situ Graft Replacement for Mycotic Thoracic Aortic Aneurysm after Stent-Grafting - Inoue, Ryozo; Kaneda, Kozo; Oka, Katsuhiko; Morishima, Atsutomo; Nishiwaki, Noboru (Japanese Journal of Vascular Surgery, 2011)
We report a successful surgical case of in situ graft replacement for mycotic thoracic aortic aneurysm following stent-grafting. A 76-year-old woman with hemosputum for 3 months was admitted to our hospital. Computed tomography (CT) revealed a pseudoaneurysm of the thoracic descending aorta. There were no infectious findings and we therefore performed stent-grafting of the lesion to prevent possible rupture. The patient was discharged on postoperative day 12, but 4 months later, she began vomiting blood and was immediately readmitted. Gastric endoscopy revealed bleeding from an ulcerous lesion, which was determined to be a Group V ulcer based on histopathological findings. Although the bleeding subsided, she again vomited blood 1 week after endoscopic hemostasis. However, on this occasion gastric endoscopy revealed no signs of bleeding. Emergency CT revealed enlargement of a thoracic descending aortic aneurysm, while laboratory findings showed an enhanced inflammatory reaction and a high fever. We diagnosed hemoptysis due to mycotic thoracic aortic aneurysm. We removed the stent-graft and replaced it with a prosthesis soaked in rifampicin. On postoperative day 33, the patient experienced lumbar pain and difficulty in walking. She also had an extradural abscess and underwent abscess drainage. The patient was discharged on postoperative day 190 and experienced no recurrence of infection for 18 months postoperatively. The indications of stent-grafting for aortic aneurysm should be carefully considered.